Potensi Prosesi Balimau Kasai Sebagai Atraksi Wisata Budaya Dalam Melestarikan Adat DanBudaya Di desa Batu Belah Kecamatan Kampar Kabupaten Kampar - Sabri, Afisi; Marlina, Leni (Jurnal Daya Saing, 2015)
Abstract: Kampar regency has the potential of culture as a source of tourism Based on the findings, the conclusions of this study is that the potential Procession Balimau Kasai For Tourism Attractions Culture, among others, have the potential to be developed in any event to welcome the month of Ramadan. The procession potential Balimau Kasai For Tourism Attractions Culture as a cultural tourist attraction, namely: Attracting visitors or tourists; Balimau kasai a tour event as a cultural tourism attractions; and Balimau kasai a distinctive customs and culture hereditary always retained by the people in the district of Kampar. Constraints faced is the lack of coordination between all interested parties between the head region. Keywords: Procession Balimau Kasai For Tourism Cultural Attractions